1997
DOI: 10.1046/j.1365-2141.1997.2163033.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequent involvement of chromosomes 1, 3, 7 and 8 in splenic marginal zone B‐cell lymphoma

Abstract: Summary.We have studied 19 cases of splenic marginal zone B-cell lymphoma (SMZBCL) combining cytological features, conventional cytogenetics, and in situ hybridization (ISH) techniques.A clonal chromosome abnormality was found in 11/19 patients (58%). The more frequent recurrent abnormalities were: del(3), del (7q), and involvement of chromosomes 1, 3, 7 and 8. No patient showed the translocation t(11;14)(q13;q32). An outstanding finding was the low incidence of trisomy 3 (36%) compared to patients with MALT l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
24
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 7 publications
3
24
0
2
Order By: Relevance
“…4,6 The selection of cases used here, taking splenic histology into account together with the other features of the tumors, made it possible to restrict the cases included to a relatively homogeneous histological type, thus avoiding any bias arising from the selection of the sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,6 The selection of cases used here, taking splenic histology into account together with the other features of the tumors, made it possible to restrict the cases included to a relatively homogeneous histological type, thus avoiding any bias arising from the selection of the sample.…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic analysis of SMZL cases has showed diverse abnormalities at chromosomes 1, 3, 7, and 8, 4 -5 chromosome 7 being the most frequently altered (3/19 cases). 4 Some SMZL cases showed del 7q as the only cytogenetic abnormality, this chromosome loss being found in 7q22 as well as in 7q32. 4 7q abnormalities have been previously published in studies of other chronic lymphoproliferative disorders by cytogenetic techniques.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 -9 In previous studies we have reported that in some SMZL cases, the only cytogenetic abnormality displayed was del(7q) that could suggest that del(7q) is associated with SMZL. 6,10 Recently, loss of heterozygosity studies demonstrated that the frequency of allelic loss in SMZL (40%) is higher than that observed in other B-cell lymphoproliferative syndromes. The most frequently deleted microsatellite was D7S487.…”
mentioning
confidence: 99%
“…Cytogenetic analyses have shown involvement of chromosomes 1, 3, 7, and 8. 5,6 Fluorescence in situ hybridization studies on interphase nuclei have demonstrated the presence of trisomy 3 in a proportion of cases ranging from 18 to 47% of SMZL. 6 -9 In previous studies we have reported that in some SMZL cases, the only cytogenetic abnormality displayed was del(7q) that could suggest that del(7q) is associated with SMZL.…”
mentioning
confidence: 99%